2023
DOI: 10.3390/ijms24119156
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Urinary Peptide and Proteomic Biomarkers in Chronic Kidney Disease: A Systematic Review

Abstract: Biomarker development, improvement, and clinical implementation in the context of kidney disease have been a central focus of biomedical research for decades. To this point, only serum creatinine and urinary albumin excretion are well-accepted biomarkers in kidney disease. With their known blind spot in the early stages of kidney impairment and their diagnostic limitations, there is a need for better and more specific biomarkers. With the rise in large-scale analyses of the thousands of peptides in serum or ur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 144 publications
0
3
0
Order By: Relevance
“…TF, CP and NGAL were isolated in the urine of pediatric patients with active LN, using proteomics studies. 7,16 Unlike other sample sources (serum or tissue), obtaining urine is not an invasive procedure, and it can be easily collected, allowing for sequential sampling. In the case of LN, the urine is physically close to the site of activity of the disease, being an interesting sample for monitoring of patients with LN.…”
Section: Discussionmentioning
confidence: 99%
“…TF, CP and NGAL were isolated in the urine of pediatric patients with active LN, using proteomics studies. 7,16 Unlike other sample sources (serum or tissue), obtaining urine is not an invasive procedure, and it can be easily collected, allowing for sequential sampling. In the case of LN, the urine is physically close to the site of activity of the disease, being an interesting sample for monitoring of patients with LN.…”
Section: Discussionmentioning
confidence: 99%
“…NS has a complex pathogenesis with multiple case types, and there are no accepted biomarkers. In this regard, numerous studies have identified urine protein biomarkers, which show promise in the diagnosis of NS, including vitamin D binding protein, neutrophil gelatinase-associated lipocalin, CD80, , but most of these studies were conducted in children and did not yield consistent results. There is a lack of systematic research on searching for biomarkers in blood system, and the assay based on circulating markers may detect NS at early stage, particularly in conjunction with urine-based biomarker test.…”
Section: Introductionmentioning
confidence: 99%
“…T he increasing burden of chronic diseases indicates the need for noninvasive, easily accessible, stable, and cost-effective biomarkers. The field of urinary proteomics/peptidomics has developed extensively and consistently over the past two decades, with a focus on kidney and cardiovascular diseases [1][2][3][4][5][6]. Thousands of proteins present in the human body are ultimately degraded by ubiquitous proteolytic enzymes, resulting in the generation of protein fragments, that is, peptides.…”
Section: Introductionmentioning
confidence: 99%